The effect of feed supplementation with a copper‐glycine chelate and copper sulphate on selected humoral and cell‐mediated immune parameters, plasma superoxide dismutase activity, ceruloplasmin and cytokine concentration in broiler chickens. Issue 1 (12th June 2017) - Jarosz, Ł. S.; Marek, A.; Grądzki, Z.; Kwiecień, M.; Kaczmarek, B.
Summary: The varied bioavailability and different effects of organic forms of copper on the immune system of poultry have prompted the search for new feed additives based on copper compounds containing modified chelate complexes. The aim of the study was to determine the effect of inorganic and organic forms of copper on selected parameters of the cellular and humoral immune response in broiler chickens by determining the percentages of CD3 + CD4 +, CD3 + CD8 + and CD25 + lymphocytes, cells with MHC Class II expression, and BU‐1 + cells, as well as the concentrations of SOD, IL‐2, IL‐10 and TNF‐α in the peripheral blood. The experiments were conducted using 500 one‐day‐old Ross 308 roosters divided into five groups. Cu was added in inorganic form (CuSO4 ), in inorganic form with the addition of phytase (CuSO4 + F), in organic form in combination with glycine (Cu‐Gly) and in organic form in combination with glycine and a phytase supplement (Cu‐Gly+F). The results of the study indicate an increase in the percentage of CD3 + CD4 + and CD3 + CD8 + T lymphocytes, CD25 + T cells, and cells expressing MHC class II molecules, and in the concentration of ceruloplasmin, activity of superoxide dismutase and the concentration of IL‐2 in the groups that received copper, particularly copper‐glycine chelates. Based on the study, we can conclude that supplementation of poultry feed with copper chelates activates mainly the Th1 cellular immune response and the response of peripheral blood T lymphocytes. Furthermore, it promotes secretion of cytokines, which are involved in potentiation and regulation of the immune response in birds.